Design of Bi-functional mixed oxide electrodes for selective oxidative C-C cleavage of glycerol to formate and synchronized green hydrogen production - Saha, Arindam; Murugiah, Vasantharadevi; Ranjan, Ravi; Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Saha, Avisekh; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2024)
Alkaline water electrolysis is a mature method to produce green hydrogen; however, it suffers from significantly high cost as high overpotentials are required for the oxygen evolution reaction (OER). However, the OER could be avoided altogether by replacing it with kinetically favorable oxidation of abundantly available feedstock molecules at a significantly low potential to value-added product(s) together with green hydrogen generation. This is a potential method to address the high cost of green hydrogen production while converting waste to wealth. Herein, we report green, template-free hydrothermal synthesis of an electrochemically active NiCoMn mixed oxide (NCMO) electrocatalyst with multiple sites, porous structure, large surface area, and nanoneedle (NN) morphology deposited directly over Ni foam (NF). Sustainable electrocatalytic performance was demonstrated for 120 h in 0.2 M alkaline glycerol using chronoamperometry and chronopotentiometry. Highly selective formate production demonstrated an exclusive C-C cleavage with the present catalyst system. Oxides of individual metal-ions (Ni, Co, and Mn) and their bimetallic combination (NiCo, NiMn, and CoMn) exhibited lower activity and product selectivity than the trimetallic NCMO electrocatalyst. The membrane-free two-electrode electrolyzer setup with NCMO/NF at both the anode and cathode (NCMO/NF & Vert;NCMO/NF) requires 1.63 V to accomplish 100 mA cm-2 with 0.2 M glycerol, which is 296 mV less than that of 1 M KOH solution. High faradaic efficiency was observed for hydrogen (98%) with highly selective formate (90%) production. Electrocatalytic formate generation from an alkaline glycerol solution with NCMO is an energy-efficient and promising approach that also supplies carbon-negative green H2. NiCoMn oxide nanoneedles with a cactus-like morphology are shown as bifunctional electrocatalysts that selectively oxidize glycerol to HCOOH and concurrently produce H2.

Fuel-influenced nanorod-to-nanosphere transformation of vanadium-doped ZnO and its performance in dye-sensitized solar cells - Kuppusamy, Sasikumar; Mohan, Theanmozhi; Gnana Kumar, G.; Gopinath, Chinnakonda S.; Saha, Arindam; Michael, Robin Jude Vimal (NEW JOURNAL OF CHEMISTRY, 2024)
Keywords: Nanoparticles; Nanowires; Photoanode; Thin-films

Growth of Mo-doped Ni3S2 nanorods array for superior overall water splitting reaction - Sharma, Pooja; Khandare, Lina; Saha, Arindam; Chaure, Nandu B.; Yengantiwar, Ashish (International Journal of Hydrogen Energy, 2025)
Designing novel, efficient and cost-effective dual-functional electrocatalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) using an alkaline electrolyte is crucial for establishing a sustainable hydrogen economy and transitioning to a society powered by renewable energy sources. In the present work, Mo-doped nickel sulfide (Mo-Ni3S2) nanorods were grown on Ni-treated nickel foam (N-NF) substrate via a two-steps hydrothermal method. Specifically, Mo-Ni3S2/N-NF surface consists of nanorods-like morphology, which provides extensive area for percolation of electrolyte, that resulting in outstanding catalytic performance. Such a well-synthesized electrode exhibited superior performance and stability for OER as compared with pristine Ni3S2/NF and bare nickel foam (NF) electrodes. In addition, Mo-Ni3S2/N-NF electrode provides good HER activity and confirms its dual-functionality in alkaline medium. Our champion Mo-Ni3S2/N-NF electrocatalyst delivers best OER overpotential of 230 mV at current density of 100 mA/cm(2). Also, it provides HER overpotential of 100.6 mV at a current density of 10 mA/cm(2). Both OER and HER are carried out in the presence of 1 M KOH alkaline electrolyte. OER stability of the best-performed Mo-Ni3S2/N-NF electrode demonstrates almost constant current density similar to 120 mA/cm(2), which retains 90% of original value after continuously tested for the duration of 22 h. The total cell voltage of 1.56 V is provided by Mo-Ni3S2/N-NF integrated system and it demonstrates a good stability for duration of 22 h. Our approach provides a new insight into developing earth-abundant, inexpensive and superior dual-functional electrocatalyst for overall water splitting reaction (WSR).
Keywords: Dual-functional electrocatalyst; HER; Mo doping; Nickel sulfide nanorods; OER; overall water splitting

Multifunctional NiO/Ti3+-TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e- and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p-n heterojunction formation between NiO and Ti3+-TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+-TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni-Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+-TiO2 nanocomposites. EXAFS studies show that the Ni-O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+-O-Ti3+/Ti4+ lattice network. Ni2+/Ti3+-TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C-C cleavage of glycerol. The NiO/Ti3+-TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+-TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h-1 g-1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+-TiO2, formation of a p-n heterojunction at the interface between NiO and Ti3+-TiO2 and effective utilization of charge carriers for redox reactions.

Selective anodic transformation of glycerol with ZnCo 2 O 4 2D nanoplates: sustainable coproduction of carbon-negative green hydrogen and formic acid - Saha, Arindam; Murugiah, Vasantharadevi; Kollenteakathootu, Jayalakshmi; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2025)
In the pursuit of sustainable green hydrogen production, the electrooxidation of abundantly available carbon-containing molecules at a significantly low voltage presents a promising pathway, helping to reduce the cost of hydrogen generation while simultaneously yielding value-added chemicals/fuels. In the current study, we report the template-free green synthesis of ZnCo2O4 directly on Ni-foam (NF), demonstrating anodic stability and bifunctional electrocatalytic activity toward alkaline (1 M KOH) glycerol oxidation over an extended duration of 230 h at 50 mA cm- 2. The catalyst's high electrochemical surface area contributes to its remarkable performance, enabling sustained high current density. Compared with monometallic (ZnO or Co3O4) oxides, ZnCo2O4 oxide reveals superior catalytic performance. The two-electrode electrolyzer setup (ZnCo2O4 oxide/NF || ZnCo2O4 oxide/NF) operates at a significantly low cell potential of 1.9 V to achieve 100 mA cm- 2 in 0.2 M glycerol, which is 180 mV lower than that of conventional 1 M KOH solution. The three-electrode setup achieved 1 A/cm2 current density at 1.907 V vs RHE. Both anodic and cathodic processes exhibit high Faradaic efficiency, achieving 98% efficiency for H2 and 90% selectivity toward formate generation, along with significant methanol production. This demonstrates efficient C-C bond cleavage capability with glycerol to predominantly C1-products. The electrocatalytic formate production from alkaline glycerol using ZnCo2O4 offers an energy-efficient pathway, facilitating carbon-negative green hydrogen generation, thus contributing to a cleaner and sustainable energy landscape.
Keywords: energy conversion; Formic acid; glyceroloxidation; green H-2; water electrolysis

Steric hindrance modulated efficient thermally activated delayed fluorescence with non-linear optical, ferroelectric and piezoelectric properties - Dutta, Madhusudan; Chatterjee, Abhijit; Deka, Nilotpal; Tanwar, Riteeka; Mishra, Vishnu; Saha, Arindam; Mandal, Pankaj; Boomishankar, Ramamoorthy; Hazra, Partha (Chemical Science, 2025)
Multi-carbazole-based benzonitrile systems are efficient thermally activated delayed fluorescence (TADF) materials for organic light-emitting diodes (OLEDs). However, they suffer from low PLQY due to the large dihedral angle arising from steric crowding. Addressing this challenge, we demonstrate a potent strategy to engineer steric crowding in this work. To achieve our goal, we have designed three luminogens, namely, CzPHCN, tCzPHCN and Cz2CzPHCN based on phenanthrene-9,10-dicarbonitrile (PHCN), as an acceptor core to minimize the steric hindrance between the donor groups. Among the three luminogens, tCzPHCN exhibits a maximum PLQY of 86% and the highest RISC rate of 3.5 x 105 s-1, the underlying cause being the least dihedral angle of 45.72 degrees and suppressed intermolecular interaction due to the presence of the bulky tert-butyl group. Interestingly, our QM/MM calculations and experimental evidence suggest that the RISC process of both CzPHCN and tCzPHCN takes place via a hot exciton channel. Unlocking a new realm of applications, the unique non-centrosymmetric space group (Cmc21) of CzPHCN offers excellent SHG with a chi(2) value of 0.21 pm V-1 at 1320 nm. In addition to this, the molecule depicts good ferroelectric (PS = 0.32 mu C cm-2), piezoelectric energy harvesting (VOC = 2.8 V) and two-photon absorption properties.

Unified photoredox-catalyzed aerobic oxidative dynamic kinetic asymmetric transformation for C-N atropoisomers mediated by chiral organophosphites - Saikia, Pinku; Aarthika, M.; Bhattacharjya, Ayantika; Maity, Susmita; Bajpai, Priyam; Bera, Asish; Saha, Arindam; Gonnade, Rajesh G.; Vanka, Kumar; Maity, Pradip (Organic Letters, 2025)
The synthesis of anilides with a chiral C(=O)-N axis has relied on direct installation of the chiral C(sp2)-N(sp2) bond or enantioselective modification of the peripheral groups. However, these methods are constrained by the size and type of functional groups compatible with each strategy. Herein, we report a dynamic kinetic asymmetric transformation (DYKAT) for the aerobic oxidation of iminium ions to access C(=O)-N axial chirality that addresses those limitations. Furthermore, it eliminates the need for any auxiliary functional groups, which enables us to develop a unified method for the synthesis of atroposelective isoquinolone, lactam, and amide.